Nomination practice in Malaysia: A review on the requirements and conditions from Islamic perspective. - Mohd Khairy Kamarudin; Azwan Abdullah; Siti Fariha Muhamad (2015)
Nominationis an important instrument in the estateplanning. There are a few institutions offering this instrumentto assistthe heirs acceleratingthe process of claimingdeceased’sestatesuch as Employee Provident Fund(EPF), Pilgrimage Fundand Takafulcontribution. The nomineehas the responsibilitytoclaimthe fundand distributeit to the legal heirs in line withIslamic law of inheritance (faraid). However, most of the nominees fail to fulfill their responsibility appropriately. Thus, the purpose of this study is to review the conditions and requirement of nominee. The finding shows few issues have to be taken into consideration in the process of nomination and several circumstances due to irresponsible nominees.This study suggests the respective authorities to undertake additional effort in increasing the public awareness on these matters and the laws and regulations must be enacted.